Interleukin-6 Levels to Identify Patients at Risk of Early Postoperative Complications after Open Radical Cystectomy: A Clinical Study - Horosz, Bartosz; Malec Milewska, Malgorzata; Jutel, Marek; Gajdanowicz, Paweł; Van Elst, Dries; Pirożyński, Michał (International Journal of Innovative Research in Medical Science, 2023)
Background and Objective: Molecular data indicate that immune mechanisms are affected by surgical trauma. We performed a study to compare lymphocyte Th1/Th2 cytokine production profile in open cystectomy patients who developed early postoperative infectious and cardiac complications and patients whose postoperative course was uneventful. Methods: Perioperative and laboratory data of 54 patients who underwent elective open radical cystectomy with ileal conduit were assessed. Interleukin (IL)-2, IL-4, IL-5, IL-6, IL-10, IL-13, interferon - gamma (INF)-γ and tumor necrosis factor - alpha (TNF)-α concentrations were analysed at two points: before surgery and on postoperative day one (POD-1). Cardiac troponin levels on POD-1 were also analysed. Cytokine levels were determined using cytometric bead array and flow cytometry. Complications assessed as one composite outcome were pneumonia, surgical site infection and myocardial injury. Cytokine levels at two study points in patients with and without complications, as well as in patients with and without perioperative blood transfusion were compared. Results: Data from 54 cases (30% women) were analysed. Of eight assessed cytokines only IL-6 and IFN- γ levels differed at two study points. Seven patients developed infection and myocardial injury was diagnosed in six cases. Postoperative IL-6 levels increased postoperatively and were significantly higher in patients who developed complications (413.2 vs 250.2pg/ml, p=0.01), as well as in those transfused perioperatively (328.3 vs 160.2pg/ml, p=0.005). Conclusions: Open cystectomy results in major rise in proinflammatory IL-6, with higher levels in patients who develop postoperative complications and those requiring blood transfusion.